An Investigation of Cyberloafing among EFL Learners - Naura, Melva; Supriusman, Supriusman; Indah Tri Purwanti (Lectura : Jurnal Pendidikan, 2025)
This study investigates cyberloafing among EFL learners in English Department in university at Pekanbaru, focusing on how students use digital devices for non-academic purposes during class. The aims of this study are to assess the level of cyberloafing and identify the reasons why do EFL learners engage in cyberloafing. The subject of this study was selected through cluster random sampling and convenience sampling. The total number of the sample was 71 students for the quantitative study and 10 students for the qualitative study. The study adapted explanatory sequential mixed-method design. The data were collected through 35 items questionnaire and semi-structured interview. The researcher employed descriptive analysis in terms of means for the quantitative data using SPSS 29 and thematic analysis for the qualitative data. The results revealed a high level of cyberloafing, with the most common activities being sharing followed by real time updating and accessing online content. It also showed contributing factors to cyberloafing including lecturer-related reasons, such as monotonous teaching methods, course-related reasons like unengaging peer-presentations, and student-related reasons including boredom and short attention spans. The study concluded that reducing cyberloafing may be achieved by improving teaching strategies, incorporating engaging digital tools and managing structured peer-presentations. It is suggested that lecturers establish a clear digital device policy during class, students promote self-regulation learning, and further research may explore long-term consequences of cyberloafing to mitigate cyberloafing behavior in educational settings.